Mulberry leaves and their potential effects against cardiometabolic risks: a review of chemical compositions, biological properties and clinical efficacy - Thanchanit Thaipitakwong; Surawej Numhom; Pornanong Aramwit (Taylor & Francis Group, 2018)
Context: Cardiometabolic risks are regarded as the crucial factors associated with type 2 diabetes (T2DM) and cardiovascular diseases (CVD). Regarding an increased attention to medicinal plants in the current healthcare system, the effects of mulberry (Morus spp., Moraceae) leaves on cardiometabolic risks have been consecutively considered in scientific research. Objective: The present review compiles and summarizes the chemical compositions, biological properties and clinical efficacy of mulberry leaves that are related to the amelioration of cardiometabolic risks. Methods: Published English literature from the PubMed, Science Direct and Google Scholar databases was searched by using 'mulberry leaves' 'Morus spp.', 'hyperglycemia', 'hyperlipidemia', 'obesity', 'hypertension', 'oxidative stress', 'atherosclerosis' and 'cardiovascular diseases' as the keywords. The relevant articles published over the past two decades were identified and reviewed. Results: Mulberry leaves contain numerous chemical constituents. 1-Deoxynojirimycin (DNJ), phenolics and flavonoids are the prominent functional compounds. Preclinical and clinical studies showed that mulberry leaves possessed various beneficial effects against cardiometabolic risks, including antihyperglycaemic, antihyperlipidaemic, antiobesity, antihypertensive, antioxidative, anti-inflammatory, anti-atherosclerotic and cardioprotective effects. Conclusions: Mulberry leaves could be a promising therapeutic option for modulating cardiometabolic risks. However, further investigations should be performed to substantiate the potential of mulberry leaves in practical uses.